Comparison of ANB Angle with YEN Angle and W Angle for Assessing Sagittal Skeletal Discrepancy Among the Patients Attending in The Department of Orthodontics, BSMMU (Journal of Dentistry and Allied Science, 2025)
Background: Accurate assessment of sagittal jaw discrepancies is essential in orthodontic diagnosis and treatment planning. Although the ANB angle is widely used, it has limitations due to its sensitivity to positional changes of craniofacial landmarks. This study compared the ANB angle with two newer parameters, the YEN angle and W angle, across skeletal Class I, II, and III malocclusions to evaluate their reliability and diagnostic value. Methods: A cross-sectional study was conducted on 90 patients aged 18–25 years. Lateral cephalograms were grouped into Class I, II, and III according to the ANB angle. Each radiograph was traced for SNA, SNB, ANB, YEN, and W angles. Normality was tested, and comparative analyses were performed using unpaired t-tests and ANOVA. Correlation analyses and reliability testing (Cronbach’s alpha) were carried out to assess the consistency and diagnostic accuracy of the three parameters. Results: Age distribution did not differ significantly across sexes or malocclusion groups. Statistically significant differences in SNA, SNB, ANB, YEN, and W angles were observed between skeletal classes. The ANB angle showed negative correlations with both the YEN and W angles, while W and YEN angles demonstrated strong positive correlations. Reliability testing revealed the W angle (α = 0.951) to be the most consistent, followed by the YEN angle (α = 0.943) and ANB angle (α = 0.836). Conclusion: The W angle proved to be the most reliable tool for assessing sagittal skeletal discrepancies, followed by the YEN angle. Incorporating these alongside the ANB angle can improve diagnostic accuracy in orthodontic practice.Journal of Dentistry and Allied Science, Vol. 8 No 2: 20-27